Alterations in HPA-axis and autonomic nervous system functioning in childhood anxiety disorders point to a chronic stress hypothesis. (January 2015) - Dieleman, Gwendolyn C.; Huizink, Anja C.; Tulen, Joke H.M.; Utens, Elisabeth M.W.J.; Creemers, Hanneke E.; van der Ende, Jan; Verhulst, Frank C.
Highlights: Children with AD have specific psychophysiological characteristics, which resemble the psychophysiological characteristics of chronic stress. A high clinical burden is associated with altered ANS and HPA-axis functioning. Children with specific phobia can be discerned from children with social phobia and separation anxiety disorder on higher skin conductance level. Summary: Background: It is of debate whether or not childhood anxiety disorders (AD) can be captured by one taxonomic construct. This study examined whether perceived arousal (PA), autonomic nervous system (ANS) and hypothalamic–pituitary–adrenal (HPA) axis measures can distinguish children with different primary diagnoses of clinical anxiety disorders (AD) from each other, and from a general population reference group (GP). Methods: The study sample consisted of 152 AD children (comparing separation anxiety disorder, generalized anxiety disorder, social phobia and specific phobia), aged 8- to 12-years, and 200 same-aged reference children. HPA-axis functioning was measured by a diurnal cortisol profile. ANS functioning was measured by continuous measures of skin conductance level in rest and during a mental arithmetic task and high frequency heart rate variability in rest. PA was assessed by a questionnaire. Results: The AD sample showed lower high frequency heart rate variability during rest, heightened anticipatory PA, higher basal and reactive skin conductance levels and lower basal HPA-axis functioning compared to the GP sample. The existence of three or more clinical disorders, i.e. a high clinical 'load', was associated with lower basal HPA-axis functioning, higher skin conductance level and lower posttest PA. Specific phobia could be discerned from social phobia and separation anxiety disorder on higher skin conductance level. Conclusions: Our findings indicated that children with AD have specific psychophysiological characteristics, which resemble the psychophysiological characteristics of chronic stress. A high clinical 'load' is associated with an altered ANS and HPA-axis functioning. Overall, ANS and HPA-axis functioning relate to AD in general, accept for specific phobia.